Using field spectroscopy combined with synthetic aperture radar (SAR) technique for detecting underground structures for defense and security applications in Cyprus - Melillos, George; Themistocleous, Kyriacos; Papadavid, George; Agapiou, Agapios; Kouhartsiouk, Demetris; Prodromou, Maria; Michaelides, Silas; Hadjimitsis, Diofantos G. (My University, 2017)
This paper aims to investigate different methods for the detection of underground concrete structures using as a case study an area of abandoned military bunkers. Underground structures can affect their surrounding landscapes in different ways, such as alter the moisture capacity of soil, its composition and the vegetation vigor. The latter is often observed on the ground as a crop mark; a phenomenon which can be used as a proxy to denote the presence of underground nonvisible structures. A number of vegetation indices such as the Normalized Difference Vegetation Index (NDVI), Simple Ratio (SR) and Enhanced Vegetation Index (EVI) were utilized for the development of a vegetation index-based procedure aiming at the detection of underground military structures by using existing vegetation indices or other in-band algorithms. One of the techniques examined is that of the C-Band Synthetic Aperture Radar (SAR), which provide information on the vegetation height based on the analysis of the difference between areas of buried structures and reference areas.
Keywords: EVI; NDVI; Remote sensing; SAR; Spectroscopy; SR; Underground structures; Vegetation indices